Analyzing Students' Entrepreneurial Intentions: The Influence of Entrepreneurial Motivation and Adversity Quotient - Rahmawati, Rahmawati; Hamdani, Nizar Alam; Maulani, Galih Abdul Fatah (Entrepreneurship Faculty, Universitas Garut, 2025)
This study discusses how much influence entrepreneurial motivation has on entrepreneurial intention through the adversity quotient. The population of this study were students of the Faculty of Entrepreneurship, Garut University. This type of research is quantitative research with a descriptive approach. The sample used in this study was 165 students, using purposive sampling technique and using the supporting tool Smart PLS version 3.2.9 by distributing questionnaires which were then collected by google form link. The purpose of this study is to examine the effect of entrepreneurial motivation on entrepreneurial intention through the adversity quotient. This research is intended to find out the mediating variables that are able to influence entrepreneurial intention in addition to the research that has been done before. The analysis used in this study is the outer model test, inner model test and hypothesis testing conducted using direct effect, indirect effect and total effect. The results of this study state that entrepreneurial motivation has an influence of 42.6%. The adversity quotient variable has an influence of 45.2% on entrepreneurial intention, and the entrepreneurial motivation variable has an influence of 48.4% on adversity quotient. These three variables show that a variable is able to influence each other with a sufficient or moderate value. aims to examine the effect of entrepreneurial motivation on entrepreneurial intention through adversity quotient.